Modelling for the Reduction and Spread Transmission of the Dynamics and Control of Zika virus Disease: Using Ordinary Differential Equations - G. Adamu; A.S. Ndagara; M. Mamuda; I.U. Omatola (Journal of Applied Sciences and Environmental Management)
The Zika virus is a flavivirus which upon infection in humans causes an illness known as Zika fever. It is commonly identified by popular rash, mild fever and arthritis. The Zika virus (ZIKV) was first identified and isolated from the Zika forest in Uganda in 1947. This paper focuses on human recovery from treatment and death of mosquitoes from insecticides in order to reduce the spread of the virus. This shows that the ZIKV is endemic in a population when the illness exists and is a threat to a population if there is no control. Therefore, the model formulated is unique for analysis. The result of this study shows that the treatment technique without insecticides has no significant reduction in the infected vectors and hosts. The stability of the disease shows stable with Ro > 1. Finally, the best option is to use an insecticide to reduce the spread of the virus on both infected hosts and vectors.